Immigrant Background and Rape Conviction: A 21-Year Follow-Up Study in Sweden - Khoshnood, Ardavan (Journal of interpersonal violence, 2026)
While extensive research exists on the severe consequences among rape victims, little is known about specific predictors in relation to rape convictions among immigrants to Europe. This study from Sweden (having one of Europe’s highest per capita rates of rape) investigates individuals convicted of rape, aggravated rape, attempted rape, or attempted aggravated rape, collectively termed as rape+, against women 18 years or older, from 2000 to 2020. In this case-control study, we analyzed data from Swedish population-based registers. The analysis includes 4,032 individuals convicted of rape+ and 20,160 matched controls. We used logistic regression models to examine the relationship between immigrant background and rape+ convictions, while adjusting for several potential confounders. We found that 36.9% of the convicted individuals and 69.5% of the controls were Swedish-born with two Swedish-born parents. The odds of being convicted of rape were higher for individuals with an immigrant background across all models. After adjusting for potential confounders (socioeconomic status, substance use disorders, psychiatric disorders, and criminal behavior), these odds decreased but remained significant, especially for those born outside Sweden and arriving at age 15 or older. Our findings reveal a strong link between immigrant background and rape convictions that remains after statistical adjustment. The mechanisms behind the overrepresentation of individuals with an immigrant background among those convicted of rape+ need further exploration.